How volatile are exchange rates? - Wali, Muammer; Manzur, Meher (School of Economics and Finance, Curtin Business School, Curtin University, 2011)
This paper briefly describes the broad features of major exchange rates since the early 1970s, and compares these features with those of the 1960s. Also included is a brief analysis of whether these features are manifested in real interest rates and in commodity prices, with seemingly curious results